Rare case of intramuscular hemangioma of infraspinatous muscle - Naik, Narendra G.; Karandikar, Sangram (International Journal of Research in Medical Sciences, 2017)
Intramuscular hemangiomas are rare benign neoplasms accounting for <1% of all hemangiomas. Intramuscular hemangiomas are relatively uncommon and frequently misdiagnosed, due to their vague presentations. In any patient with soft-tissue mass suspected of a hemangioma, MR imaging may provide very specific information regarding the characteristics, the origin, and the extent of the lesion than other imaging modalities. The definitive diagnosis is made by histopathological study of the surgical specimen. Here, we present a case report of intramuscular hemangioma occurring in the left infraspinatous muscle in an 18-year-old boy. Due to rare nature of such lesions, the patient's diagnosis was delayed and patient was treated for chronic pain in left shoulder joint. Magnetic resonance imaging finally clinched the diagnosis and patient was successfully operated upon and subsequently cured.